Peer characteristics and substance use among high school students - Erdem, Gizem; Y. Eke, Ceyda (Journal of Dependence, 2006)
Objective: The goals of this study are to determine peer characteristics of high school students and evaluate environmental factors that increase their risk of substance use. In addition to that, it is aimed to display peer characteristics of substance users. Method: As a scope of Youth Research, 43 schools were randomly selected among 15 districts of İstanbul. 3842 questionnaires were administered to 10th grade students between March – May 2004. 3168 questionnaires were valid. In this article, questionnaires sections regarding peer characteristics and substance use are evaluated. Results: It has been found that lifetime prevalence of tobacco and alcohol use are %34.3 and %49.7 respectively, and of any other substance use is %14.3. Among peer characteristics that increase the risk of substance use, having a drug-user peer is found to be prominent. Those who have substance user friends are at 6 times higher risk of using drugs. In addition to that, compared to girls, boys are at 2.5 times more risk of having friends who engage in trouble with police and theft and 2 times more likely to have friends that intentionally damage other people’s property. But risk of having antisocial peers is higher for substance user girls, than boys. For instance, girls who stated that they have used drugs are 6.6 times higher at risk of having friends committing theft whereas this risk is at 3.3 times for boys. %50.2 of substance users have substance user peers whereas %15.2 of non-users do so. Conclusion: For purpose of making detailed analysis of peer influence, this study should be replicated taking into account the structure of risky peer group. Peer influence as a risk factor should be re-evaluated by making gender based comparisons.